2D Storytelling:Halal label among the society - Nurul Ainul Mardhiah Harun; Dr Azir Redza Norizan (Journal of Computing Technologies and Creative Content, 2022)
On the product packaging, halal label writings or statements are halal, implying that the product is halal. Halal awareness refers to understanding the purpose and advantages of consuming and using halal products. For Muslims, halal is important in terms of food preferences because we must follow the religious permissible or lawful. The aim of this study is to educate the young generation about the importance of checking the ingredients and halal logo before purchasing a product or eating a meal. We decided to create a 2D animation that will educate the younger generation about the halal concept while also determining how well Malaysian youth understand and practice halal. To explain more about the halal labels or halal logos, we chose to create a storytelling 2D animation. The ADDIE Model, which was used in this study, will be amended in this study.